BESS for frequency control in systems with high penetration of wind energy (2017)
The wind power penetration into the system, as other intermittent energy sources, have impacts in grid frequency performance that lead to increase system reserve and to reduce the power extraction in the wind turbines. In this document, an integration analysis of the Battery Energy Storage System (BESS) is presented with its dynamics characteristics, This in order to identify the optimal size of an aggregated system in order to support frequency regulation. Once the large potential for the provision of frequency control services is identified, in this document the batteries are used to increase the frequency performance of the grid. The primary frequency control presented takes into account the dynamic response of the integrated system with wind turbines and BESS, while the LFC have a robust performance due to system inertia uncertainties.